Association of fungal secondary metabolism and sclerotial biology - Calvo, Ana M.; Cary, Jeffrey W. (Frontiers in Microbiology, 2015)
Fungal secondary metabolism and morphological development have been shown to be intimately associated at the genetic level. Much of the literature has focused on the co-regulation of secondary metabolite production (e.g. sterigmatocystin and aflatoxin in Aspergillus nidulans and Aspergillus flavus, respectively) with conidiation or formation of sexual fruiting bodies. However, many of these genetic links also control sclerotial production. Sclerotia are resistant structures produced by a number of fungal genera. They also represent the principal source of primary inoculum for some phytopathogenic fungi. In nature, higher plants often concentrate secondary metabolites in reproductive structures as a means of defense against herbivores and insects. By analogy, fungi also sequester a number of secondary metabolites in sclerotia that act as a chemical defense system against fungivorous predators. These include antiinsectant compounds such as tetramic acids, indole diterpenoids, pyridones and diketopiperazines. This chapter will focus on the molecular mechanisms governing production of secondary metabolites and the role they play in sclerotial development and fungal ecology, with particular emphasis on Aspergillus species. The global regulatory proteins VeA and LaeA, components of the velvet nuclear protein complex, serve as virulence factors and control both development and secondary metabolite production in many Aspergillus species. We will discuss a number of VeA and LaeA-regulated secondary metabolic gene clusters in A. flavus that are postulated to be involved in sclerotial morphogenesis and chemical defense. The presence of multiple regulatory factors that control secondary metabolism and sclerotial formation suggests that fungi have evolved these complex regulatory mechanisms as a means to rapidly adapt chemical responses to protect sclerotia from predators, competitors and other environmental stresses.